Validity and reliability of the 45-15 test for aerobic fitness in young soccer players - Castagna, C.; Iellamo, F.; Impellizzeri, F. M.; Manzi, V. (International Journal of Sports Physiology and Performance, 2014)
The aim of this study was to examine the reliability and validity of a popular field test for aerobic fitness used in soccer (45-15) in Italy. Alternating progressive 45-s runs with 15 s passive recovery until exhaustion, the test considers peak speed (PS) as a reflection of maximal aerobic speed (MAS). The validity and reliability of the 45-15 was assessed in 18 young male soccer players (age 16.7 ± 1.8 y, body mass 70 ± 7.45 kg, height 177 ± 0.5 cm, 55.62 ± 5.56 mL/kg·min) submitted to laboratory testing for aerobic fitness and repeatedly to the 45-15. Results showed that 45-15 PS was significantly related to VO2max (r = .80, P < .001, 95%CI .47-.93) and MAS (r = .78, P = .001, 95%CI .43-.93). No significant bias between MAS 45-15 PS (P = .11) was found during the measurement-consistency study. Receiver-operating-characteristic (ROC) analysis showed that 45-15 PS was sensitive in detecting VO2max changes in subjects as revealed by area under the curve (.97; 95%CI .73-1). Players with peak 45-15 speed equal to or above 16.5 km/h (ie, ROC cutoff) may be considered to have good aerobic fitness. In light of this study`s findings, the 45-15 test may be considered a reliable and valid test to evaluate meaningful information to direct generic aerobic training in soccer.